2011
DOI: 10.1209/0295-5075/96/66005
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical prediction of the growth and surface structure of Pt and Ni nanoparticles

Abstract: The surface structure of crystal grains determines the catalytic efficiency of metal particles. In this paper, we apply our recently established condensation potential model to predict the surface structure of Pt and Ni nanoparticles, which are used in fuel cells, showing the model works well but the Wulff construction fails. Based on first-principle calculations via this model, the surfaces of various shapes of Pt/Ni nanoparticles are mainly composed of fcc ( 111) faces (about 80%/60% of the total area). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The difference between the potential energies of the film and the bulk can be used to calculate the surface tension (γ). 77,78 In a free-standing P3HT film (a P3HT film not supported by a substrate), hexyl side chains are exposed to the surface along the z-direction (hereafter referred to as "edge-on" structure), whereas both backbone and hexyl chains are exposed to the surface along the y-direction (hereafter referred to as "face-on" structure). To calculate the surface tension (γ) of a freestanding P3HT film with edge-on or face-on structure, first the bulk P3HT system was equilibrated at 300 K in the NVT ensemble.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the potential energies of the film and the bulk can be used to calculate the surface tension (γ). 77,78 In a free-standing P3HT film (a P3HT film not supported by a substrate), hexyl side chains are exposed to the surface along the z-direction (hereafter referred to as "edge-on" structure), whereas both backbone and hexyl chains are exposed to the surface along the y-direction (hereafter referred to as "face-on" structure). To calculate the surface tension (γ) of a freestanding P3HT film with edge-on or face-on structure, first the bulk P3HT system was equilibrated at 300 K in the NVT ensemble.…”
Section: Resultsmentioning
confidence: 99%
“…In our MD simulations, a free-standing film was created by removing the periodic boundary condition of a bulk system along the direction of the surface ( z -axis/ y -axis in the present study), keeping other boundaries unchanged. The difference between the potential energies of the film and the bulk can be used to calculate the surface tension (γ). , …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the geometrical models can much faster survey a greater number of nanoparticles and nanoclusters (including nanoparticles with larger diameters and many more gold atoms in the core) much faster. Practically speaking, the presented equations and tables are easily adjustable (via the radius of the metal atom) for the determination of the composition of other metal nanoparticles with fcc lattices (Pd, Pt, Ni (Lin et al 2011 ) as well as coinage metals Ag, Cu); perhaps even alloy-type metal nanoparticles if elemental composition is determined upfront. The predicted sequences of preferred shapes by Guisbiers et al should here be tremendously helpful (Guisbiers et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding structural, magnetic, and electronic characteristics of bimetallic Pt 13−n Ni n (n = 0–13) nanoclusters, some studies have shown that Ni does not provide any significant structural deformation but can weak the nanoalloy binding energy and increase its magnetic nature ( Jia et al, 2013 ; Zhao et al, 2013 ). Concerning the WGS reaction, theoretical studies of PtNi nanoclusters with different atomic quantities of Pt and Ni have been published, exposing the possibility of using those nanoclusters as catalysts ( de Souza Monteiro et al, 2008 ; Lin et al, 2011 ; Piotrowski et al, 2012 ; Zhao et al, 2013 ; Guedes-Sobrinho et al, 2015 ; Lian et al, 2015 ; Roduner and Jensen, 2015 ; Mokkath, 2018 ). Yet for the WGS reaction, previously computed adsorption energy values suggested that CO adsorption would occur more strongly than H 2 O on Pt 3 M (M = Cu, Mo, Ni, Rh) nanoclusters ( Lian et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%